2006
DOI: 10.7547/0960283
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rearfoot-Controlling Orthotic Treatment on Dorsiflexion of the Hallux in Feet with Abnormal Subtalar Pronation

Abstract: The aim of this study was to determine whether the treatment of abnormal subtalar pronation restores functional (as opposed to structural) limited dorsiflexion of the first metatarsophalangeal joint (functional hallux limitus). We studied 16 feet of eight individuals with abnormal subtalar pronation. Orthoses were made for all of the feet, and hallux dorsiflexion was measured during weightbearing. Each patient was unshod without the orthosis, unshod with the orthosis fitted on the same day, and unshod with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…This method has been used previously in other studies. 20 Dorsiflexion and plantarflexion of the hallux IPJ were measured using the same method, adapted to this joint. The measuring instrument used in both joints was a two-arm 28 scaled goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been used previously in other studies. 20 Dorsiflexion and plantarflexion of the hallux IPJ were measured using the same method, adapted to this joint. The measuring instrument used in both joints was a two-arm 28 scaled goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…En este sentido, los momentos de pronación excesivos de la articulación subastragalina durante la fase propulsiva de la marcha van a aumentar la movilidad articular del pie, perdiendo así la capacidad de comportarse como una palanca rígida que permita de una forma correcta la propulsión y progresión del paso (25)(26)(27)(28)(29). De esta forma, el músculo peroneo lateral largo se vuelve incapaz de anclar la cabeza del primer metatarsiano al suelo al disminuir su vector de fuerza de palanca y de función plantarflexora (25,29,30). A este modelo patomecánico, debemos de sumarle que las FRS en la última fase del proceso de la marcha producen una dorsiflexión e inversión del primer metatarsiano, destacado entre las demás estructuras del primer radio (11,25,26).…”
Section: Discussionunclassified
“…The available evidence addressing this proposed mechanism of action of foot orthoses, however, is equivocal. While two studies have reported increases in first MTPJ dorsiflexion with orthoses placed under the foot in static stance [85,86], one study reported no change in first MTPJ dorsiflexion [87]. Gait studies have been similarly inconsistent, with two studies reporting a decrease in first MTPJ dorsiflexion (with medial wedging [88] and orthoses [34]) and one study reporting no change [35].…”
Section: Discussionmentioning
confidence: 99%